Konsep Ekonomi Islam Konsep Ekonomi Islam: Parameter Islamic Business Ethics (IBE) dalam Produksi: Parameter Islamic Business Ethics (IBE) dalam Produksi - Maghfiroh, Siti (el-Jizya: Jurnal Ekonomi Islam, 2020)
Human economic activity consists of three series, namely production, distribution, and consumption. However, the starting point of this activity is generally focused on production. This series must of course be in the syari’ah frame, because Islam regulates it as an activity that has norms and ethics. The reality that occurs that not all producers apply ethics to the products produced, so it needs a parameter to assess this ethical dimension. The Islamic view of product creation is to integrate aspects of ethics (morals) and trancendental components. Its implemetation is guided by the principles of Islamic business ethics, axioms of economic ethics, and a number of rules which are framed within the parameters of Islamic business ethics. The parameters of Islamic Business Ethics that can be used as a reference in production activities include three things, namely the first type of product,where a produst must h}ala>lan t}ayyiban, the goods meet maqa>sid syari’ah, and based priority needs. Second, focuses on the ethical framework of production, third gets legality from the competent authority.